The Palaearctic types of Chrysididae (Insecta, Hymenoptera) deposited in the Hungarian Natural History Museum, Budapest - Rosa, Paolo; Vas, Zoltán; Xu, Zai-Fu (Zootaxa, 2017)
A critical and annotated catalogue of the Palaearctic types of chrysidid species, subspecies and varieties deposited in the Magyar Természettudományi Múzeum is given. The lectotype of Hedychrum luculentum Förster, 1853 and the neotype of Chrysis amasina Mocsáry, 1889 are designated. Six new synonyms are proposed: Chrysis varicornis Spinola, 1838 = Chrysis cyanocoelia Mocsáry, 1889, syn. nov.; Hedychridium adventicium Zimmermann, 1962 = Hedychridium jazygicum Móczár, 1964, syn. nov.; Hedychrum cribratum Mocsáry, 1909 = Hedychrum punctigerum Mocsáry, 1909, syn. nov.; Holopyga generosa (Förster, 1853) = Holopyga hortobagyensis Móczár, 1984, syn. nov.; Holopyga turkestanica Mocsáry, 1909 = Holopyga crassepuncta Semenov, 1954, syn. nov.; and Pseudomalus cupratus (Mocsáry, 1889) = Pseudomalus meridianus Strumia, 1996, syn. nov.. One species is revalidated: Holopyga turkestanica Mocsáry, 1909, stat. resurr.. New status is proposed for: Pseudomalus cupratus (Mocsáry, 1889), stat. nov.. New combination is proposed for: Hedychridium amoenum (Mocsáry, 1911), comb. nov.. The reversal of priority is proposed for: Ellampus biaccinctus du Buysson, 1893, nomen protectum, and E. auratus var. gasperinii Mocsáry, 1889, nomen oblitum. New name is proposed for: Chrysis fusca Rosa, nom. nov. pro Chrysis ignita var. infuscata Mocsáry, 1889 nec Brullé, 1846. Pictures of eighty-nine type specimens are also provided.